Anti-troponin I antibodies in renal transplant patients - Nunes, José Pedro L.; Kaya, Ziya (Revista portuguesa de cardiologia, 2015)
Objective - To characterize the prevalence and clinical correlates of anti-troponin I antibodies in renal transplant patients. - Methods - A group of 48 consecutive renal transplant patients under immunosuppressive therapy were studied. Anti-troponin I antibodies were measured and clinical data were retrieved. - Results - An anti-troponin I antibody titer <1:40 was seen in most patients (30). IgG antibody titers ≥1:80 were seen in eight patients, with a single value of 1:160. Regarding IgM antibodies, in six cases titers ≥1:80 were seen, with one value of 1:320. In only one patient were both anti-troponin I antibody IgG and IgM titers 1:80 or higher. Clinical cardiac disease was seen in nine patients. The presence of an anti-troponin I antibody titer ≥1:80 was not associated with the presence of clinical cardiac disease (p=0.232), but was associated with statin therapy status (p=0.008), being less frequent in patients under statin therapy. - Conclusions - Anti-troponin I antibodies are seen in a minority of renal transplant patients, and are not associated with the presence of clinical heart disease, but are associated with lack of statin therapy. - Resumo - Objetivo - Caracterizar a prevalência e os aspetos clínicos associados à presença de anticorpos antitroponina I em doentes com transplante renal. - Métodos - Foi estudado um grupo de 48 doentes consecutivos com transplante renal sob terapêutica imunossupressora. Os anticorpos antitroponina I foram medidos e os dados clínicos foram obtidos. - Resultados - Um título <1:40 de anticorpos antitroponina I foi encontrado na maioria dos doentes (30 doentes). Os anticorpos IgG com títulos ≥1:80 foram encontrados em 8 doentes, com um único valor de 1:160. No caso dos anticorpos IgM, em seis casos os títulos foram ≥1:80, com um caso de título de 1:320. Apenas num doente foram os títulos dos anticorpos antitroponina I de tipo IgG e IgM simultaneamente ≥1:80. A doença cardíaca clínica existia em nove doentes. A presença de anticorpos antitroponina I com títulos ≥1:80 não se associou com a presença de doença cardíaca clínica (nível de significância 0,232), mas associou-se com a ausência de terapêutica com estatina (nível de significância 0,008). - Conclusões - Os anticorpos antitroponina I encontram-se presentes numa minoria de doentes com transplante renal, não se verificando uma associação com a presença de doença cardíaca clínica, mas com uma associação com ausência de terapêutica com estatina.